PRODUKTIVITAS PEKERJA PANEN BUAH KELAPA SAWIT (Elaeis gueineensis Jacq) DI PT. WIRA INOVA NUSANTARA, KABUPATEN KUTAI TIMUR, PROVINSI KALIMANTAN TIMUR - Bery Heriyanto; Abdul Rasyid Zarta; Jamaluddin (JURNAL AGRIMENT, 2020)
This research was motivated by the importance of workers harvesting oil palm fruit on productivity. One of the stages of oil palm cultivation is harvesting, which is one of the key determinants of oil palm productivity. Productive labor can be seen from the achievement of targets set by the company or the difference between the results obtained and the task bases that have been determined by the company. This has prompted researchers to analyze the factors that influence the productivity of oil palm harvesting workers. The purpose of this study was to analyze the effect of age, years of service, and level of education on the productivity of harvesters and to calculate the value of labor productivity in oil palm harvesting. In data analysis using descriptive method, where the data obtained from direct interviews with oil palm harvesting employees by asking several questions that have been prepared and will be processed using the SPSS method, respondents were taken as many as 35 respondents from all afdeling using the Slovin formula. The results showed that the labor productivity of oil palm harvesters at PT. WIN is significantly influenced by age and education factors. Meanwhile, tenure does not have a significant effect on labor productivity of harvesters. The productivity of harvesting labor that was achieved was 135 hrs / HOK, having exceeded the company's target of 110 hrs / HOK.